Suffering-based Medicine in the Age of Artificial Intelligence - Auro del Giglio (Brazilian Journal of Oncology)
The present paper delves into suffering-based medicine (SBM) and its potential use with artificial intelligence (AI). Suffering-based medicine provides a hermeneutical approach to patient care, allowing a deeper understanding of the subjective experiences and meaning behind a patient's suffering. With the rise of large language models (LLMs) based on deep learning, the integration of AI in the medical field has become increasingly frequent. The current study explores two cases of physicians diagnosed with cancer, utilizing SBM and an LLM, to analyze their narratives and provide a hermeneutical understanding of their suffering. Through this integration, AI can offer valuable insights into the multidimensional nature of suffering and enhance the patient-physician relationship. Further research is needed to assess the practical application and impact of this integration on patient outcomes.